Economy and Society: The Sociology of Economic Life - Carruthers, Bruce (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course introduces sociological approaches to economic institutions and behavior. The goal is to provide a set of sociological concepts and theories to interpret markets, prices, corporations, supply, demand, production, work, exchange, property, and other economic matters, in a different way. The requirements include one take-home assignment (worth 25% of the final grade) and a midterm (25%) and final exam (worth 40%). The remaining 10% will be determined by your participation in discussion sections. The take-home assignment will be given during week 3. I may modify the syllabus if and when necessary. Plagiarism and other forms of academic dishonesty will not be tolerated.